2005
DOI: 10.1002/ejoc.200500517
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Highly Diastereoselective Formation of a Novel Pentacyclic Scaffold by Direct Anodic Oxidation of 2,4‐Dimethylphenol

Abstract: Electrochemical oxidation of 2,4‐dimethylphenol directly provides pentacyclic systems being generated by an oxidative trimerization. The major pentacyclic scaffold is exclusively formed as a single diastereoisomer and is easily isolated. Three further pentacyclic compounds which occur in minor quantities were also fully characterized including their solid‐state structures. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2006)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
75
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 12 publications
4
75
0
3
Order By: Relevance
“…In addition it was possible to verify the connection between the structures of 3a [13] and 3d [14] determined by Xray crystallography and the observed NMR spectroscopic data of both diastereomers [13,14] by calculating the 1 H and 13 C chemical shifts in silico which also ensured that the crystals picked for X-ray analysis corresponded to the bulk material in every case. To achieve this, the geometries of all four possible diastereomers (Scheme 5) were optimized at the B3LYP/6-311G(d,p) level of theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition it was possible to verify the connection between the structures of 3a [13] and 3d [14] determined by Xray crystallography and the observed NMR spectroscopic data of both diastereomers [13,14] by calculating the 1 H and 13 C chemical shifts in silico which also ensured that the crystals picked for X-ray analysis corresponded to the bulk material in every case. To achieve this, the geometries of all four possible diastereomers (Scheme 5) were optimized at the B3LYP/6-311G(d,p) level of theory.…”
Section: Resultsmentioning
confidence: 99%
“…[12] In our recent research we have demonstrated that the polycyclic skeleton rac-2 can easily be obtained by oxidative coupling of 2,4-dimethylphenol using anodic oxidation (Scheme 1). [13] This reaction is the key step of a powerful methodology in a diversity-oriented synthetic approach to create multiple stereogenic centres on a multi-gram scale in a single synthetic step. [14] Furthermore, it offers access to numerous scaffolds of natural products in a highly chemo-, stereo-, regioselective and easy to perform manner.…”
mentioning
confidence: 99%
“…Methyl-substituted phenols are prone to side reactions and 2,4-dimethylphenol in particular results in predominantly polycyclic architectures upon anodic treatment. [6] To circumvent this challenge we developed a boron-based template strategy [7,8] that can be performed on larger scale. [9] A protocol for the conversion of neat phenol (1) on boron-doped diamond (BDD) electrodes was developed in our laboratory.…”
mentioning
confidence: 99%
“…[16] Dieses Dehydrotetramer des Phenols kann leicht und in großen Mengen (bis zu 23 g pro Ansatz) erhalten werden. 2 ist leicht zu isolieren, da es während der Elektrolyse in der ungeteilten Zelle ausfällt, und wird als auschließliches Diastereomer erhalten.…”
unclassified
“…Die thermische Behandlung oder -noch effizienter -die Umsetzung im Sauren von 2 [16] liefert den Spiropentacyclus 3 als alleiniges Produkt. [17] [18] erhält man das Dibenzofuran 6 als alleiniges Produkt.…”
unclassified